HE3286, an oral synthetic steroid, treats lung inflammation in mice without immune suppression - Frincke James M; White Steven K; van Heeckeren Anna M; Mangano Katia; Nicoletti Ferdinando; Pieters Raymond; Wang Angela; Conrad Douglas; Reading Christopher L; Stickney Dwight; Auci Dominick L (BMC, 2010)
Abstract Background 17α-Ethynyl-5-androsten-3β, 7β, 17β-triol (HE3286) is a synthetic derivative of an endogenous steroid androstenetriol (β-AET), a metabolite of the abundant adrenal steroid deyhdroepiandrosterone (DHEA), with broad anti-inflammatory activities. We tested the ability of this novel synthetic steroid with improved pharmacological properties to limit non-productive lung inflammation in rodents and attempted to gauge its immunological impact. Methods and Results In mice, oral treatment with HE3286 (40 mg/kg) significantly (p < 0.05) decreased neutrophil counts and exudate volumes (~50%) in carrageenan-induced pleurisy, and myeloperoxidase in lipopolysaccharide-induced lung injury. HE3286 (40 mg/kg) was not found to be profoundly immune suppressive in any of the classical animal models of immune function, including those used to evaluate antigen specific immune responses in vivo (ovalbumin immunization). When mice treated for two weeks with HE3286 were challenged with K. pneumoniae, nearly identical survival kinetics were observed in vehicle-treated, HE3286-treated and untreated groups. Conclusions HE3286 represents a novel, first-in-class anti-inflammatory agent that may translate certain benefits of β-AET observed in rodents into treatments for chronic inflammatory pulmonary disease.